2018
DOI: 10.1002/hed.25201
|View full text |Cite
|
Sign up to set email alerts
|

Narrow band imaging for risk stratification of glottic cancer within leukoplakia

Abstract: The noninvasive procedure of an NBI endoscopy may be recommended as an accurate method in predicting the risk of malignant transformation within the vocal fold leukoplakia and, therefore, would be useful in the clinic for planning the patient's therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 19 publications
0
25
0
Order By: Relevance
“…There were 398 benign lesions and 188 malignant lesions assessed in total. Four studies classified IPCL changes according the Ni 2011 classification alone 19,25‐27 . Two studies classified IPCL changes according to both Ni 2011 and ELS classification system 18,20 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There were 398 benign lesions and 188 malignant lesions assessed in total. Four studies classified IPCL changes according the Ni 2011 classification alone 19,25‐27 . Two studies classified IPCL changes according to both Ni 2011 and ELS classification system 18,20 .…”
Section: Resultsmentioning
confidence: 99%
“…However, various authors have demonstrated that NBI is still able to differentiate benign and malignant laryngeal leukoplakia with high accuracy by observing IPCL changes at the peripheries of leukoplakia 18 . Rzepakowska et al assessed 91 laryngeal lesions with leukoplakia and reported high sensitivities and specificities of 100% and 97.4%, respectively 19 . Huang et al 20 also demonstrated that NBI can differentiate between benign and malignant laryngeal leukoplakia; however, the accuracy reported was much lower.…”
Section: Introductionmentioning
confidence: 99%
“…These abnormally dilated microvessels correspond to mucosal congestion and vascular stippling in white light imaging; hence, the information provided by narrow-band imaging can counter the deficiency of white light imaging laryngoscopy when classifying vocal fold leukoplakia. In addition, with this technology, a biopsy can be avoided when predicting the pathological nature of some lesions, 15 thereby avoiding unnecessary trauma and playing an important role in the functional protection of vocal folds. Five intra-epithelial papillary capillary loop typing criteria for laryngeal lesions were first summarised by Ni et al according to the characteristic dynamic changes of intra-epithelial papillary capillary loop morphology on the mucosal surface of laryngeal lesions during the development process from a normal state to dysplasia and cancer.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 One final limitation was that our study was not randomized or controlled. Most patients with primary HPT have low 25-OH vitamin D. Replacing vitamin D has been shown potentially to decrease PTH levels and bone turnover.…”
Section: Discussionmentioning
confidence: 99%
“…Given that the mainstay of treatment for HPT remains surgical, with a number of specific techniques described and variably used, the results of this study remain applicable across a broad range of practices. 15,16 One final limitation was that our study was not randomized or controlled.…”
Section: Discussionmentioning
confidence: 99%